Mechanism analysis and experimental study for the bevelling of quartz crystal blanks - Dong, Chensong (NA, 2010)
An experimental study on the bevelling of quartz crystal blanks is presented in this paper. Based on the analysis of bevelling mechanism, the concept of critical gap height is introduced for evaluating the material removal in bevelling. The influences of seven process factors: blank quantity, powder/blank ratio, powder type, machine rpm, powder changing time, barrel diameter, and powder heating on material removal rate, bevel profile, and frequency shift were studied by Design of Experiments. It is shown from the results that 1) machine rpm has the most significant effect on material removal rate, followed by barrel diameter. Material removal rate is proportional to machine rpm and barrel diameter; 2) steeper bevel profiles can be achieved by using barrels of smaller diameter and finer powder; and 3) machine rpm has the most significant effect on the frequency shift, followed by barrel diameter and powder type. The frequency shift is proportional to the machine rpm and barrel diameter. Using finer powder can reduce the frequency shift.